Route to the temple - Temples of India Project Team (Jio Institute, 2024)
Kaner-ki-Putli Temple is located in the Khadirpur area of Bijolia, in the Bhilwara district of Rajasthan. It resides within a valley formed by water eroding the rocks within the Vindhya range. The temple is located in a secluded area close to stone quarries.